Interfacial Activity of Bitumen Components. Issue 3 (8th March 2020) - Stammitti, Aurelio; Bhanot, Ashutosh; Boza, Americo; Ng, Samson; Acosta, Edgar
Abstract: The interfacial activity of asphaltenes, naphthenic acids, and naphthenates has been amply studied in the literature, as they are involved in the formation and stabilization of bitumen and heavy crude oil emulsions. While most of the literature evaluates one component at a time, in this work these bitumen components were separated one at a time from Athabasca bitumen, and the surface activity of the resulting fraction was evaluated as a function of pH, solvent aromaticity (heptane/toluene mixtures, known as heptol, at volume ratios 50/50 and 80/20), and temperature for selected systems. The interfacial activity was evaluated in two ways: via dynamic interfacial tension during adsorption on a bitumen drop of constant volume, and via dynamic interfacial tension during drop volume cycling. The adsorption data were interpreted using a model that combined multicomponent adsorption kinetics inspired by Langmuir–Freundlich kinetics with the Fainerman surface equation of state. The volume cycling experiments were interpreted using the compression relaxation model, which segregates adsorption/relaxation effects from elastic phenomena at interfaces. Overall, the adsorption data confirmed that naphthenic acids are the fastest adsorbing species that tend to dominate the interface, but that asphaltenes adsorb, almost irreversibly, at longer time scales and likely forming a sublayer previously proposed in the literature. The dilatational elasticity of the interface seems to be highly influenced by that asphaltene sublayer, which softens at high pH at room temperature, or at 80 °C independently of the pH of the system.